Plant Community Structure of Home Gardens in Eastern Himalayan Foothills of West Bengal, India - Mohit Subba, L.; Pala, Nazir A.; Shukla, Gopal; Chakravarty, Sumit (Indian Forester, 2017)
In the present study plant community structure of eastern Himalayan foot hills home gardens in West Bengal, India was analyzed. Dominant plant species in the home gardens are Tagetes erecta, Mangifera indica and Areca catechu. Acacia auriculiformis, Artocarpus hirsutus and 19 others were sparse while Areca catechu was densest with overall numerical strength of the species in the gardens ranged from 0.02 to 62.07 individual ha-1 . Acacia auriculiformis, Artocarpus hirsutus and 18 others each were recorded with lowest IVI (0.181) and Areca catechu highest with 40.176 while Menhinick's index was 1.41. Shannon and Wiener index was inversely proportional to concentration of dominance. The gardens are diverse and heterogeneous where species are evenly distributed with higher chances of occurrence. Important timber species documented are Anthocephalus cadamba, Gmelina arborea, Michelia champaca, Shorea robusta, Switenia mahogany and Tectona grandis. Growing timber spicies in the home gardens release pressure from the surrounding forests. These home gardens are not only serving as reservoir of both cultivated and wild species but also serving as an important reservoir of short and long term stored carbon in its vegetation biomass. These gardens are also fulfilling the daily domestic substance needs of their owners along with some hard earned cash.